Knowledge, Attitude and Practice Regarding Modifiable Risk Factors of Cardiovascular Diseases Among Adults in Rural Community, Lahore - Ejaz, Sumaira; Afzal, Muhammad; Hussain, Muhammad; Sarwar, Hajra; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2018)
Background: Cardiovascular diseases (CVD) are group of disorders of heart, blood and vessels. Major risk factors are hypertension, cigarette smoking, high fat, diabetes, obesity and physically inactive. In Pakistan, prevalence data for the Cardiovascular disease is sparse, and literature indicates that there is 30-40% of all deaths in Pakistan due to cardiovascular diseases. Objective: To assess the knowledge, attitude and practice regarding modifiable risk factors of cardiovascular diseases among adults in rural community, Lahore. Methods: This was descriptive cross-sectional study. Convenient sampling was used. Data were collected from adults of rural community Lahore. The sample size was 110. KAP questionnaire was used to collect the data. Ethical permission was obtained and data was analyzed by SPSS version 21. Results: The findings of the research were good knowledge with (67%) high response of correct answer of “Smoking is risk factor of CVD”. The attitudes were negative, (28%) high correct response for “Do exercise for good health”. The practices were very poor regarding the risk-factors of cardiovascular diseases. Conclusion: The knowledge of participants towards the risk factors of cardiovascular diseases was somehow better. The attitude was comparatively negative and practices were poor. No one was following regular exercises, dietary modifications, manage stress and smoking. Rural community people should modify their lifestyle to improve their practices. There is need for health education campaign in the rural community to minimize the risk factors of cardiovascular diseases. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 76-82